Leveraging workforce flexibility to navigate platform-induced uncertainty: A study of the Italian Restaurant and hospitality sectors - Valeria Cirillo; Donato Cutolo; Dario Guarascio; Martin Kenney; Jacopo Tramontano (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2025)
As the platform economy continues to reshape the way we live, work, and consume, firms across industries are increasingly dependent upon platforms to engage with customers. Although prior research highlights how these firms develop strategic responses to cope with risks and vulnerabilities stemming from platform power, it tends to overlook how such uncertainty may affect their internal organizational structures. In this study, we examine how reliance on digital platforms influences firms' employment practices. Drawing on a comprehensive dataset from the Digital Platform Survey (DPS), administered by Italy's National Institute for Public Policy Analysis (INAPP) to over 20,000 hotels and restaurants, we find that platform participation has a positive correlation with the use of non-standard employment relationships (NSERs). Specifically, holding everything else constant, companies that rely on platforms for customer acquisition exhibit roughly 5% higher share of NSERs compared to those that do not. Multiple tests indicate that this effect varies according to structural characteristics, competitive strategies, and contextual factors that expose firms to differing levels of dependence on platforms - findings that support our conjecture of reliance on NSERs being a coping mechanism for platform-induced uncertainty. Our study advances the literature on how firms respond to the risks of platform-based intermediation and contributes to ongoing debates about the labor implications of digital transformation. As platform intermediation intensifies across sectors, these insights have important academic and policy implications.
Keywords: L22; O23; D22; D80; J21; J23; J82; 330; digital platforms; labor; platform dependence; employment relationships; Industrial organization; industrial economics; Cross-sectional large-N; survey; Power; domination; resistance